PENGARUH DIGITAL MARKETING, HARGA, DAN PROMOSI TERHADAP MINAT WISATAWAN PADA PT. SAFA WISATA INDONESIA - Nasyiwa Malia; Sabri Sabri; Samad Samad (Bisnis-Net, 2026)
This study aims to analyze the effect of digital marketing, price, and promotion on tourist interest at PT. Safa Wisata Indonesia. This research is motivated by the increasing competition in the tourism industry and the shift in consumer behavior toward digital platforms, requiring companies to optimize their marketing strategies to attract tourist interest. This study employs a quantitative method with a descriptive and associative approach. The population consists of 250 respondents, with a sample of 71 respondents determined using the Slovin formula and selected through simple random sampling. Data collection techniques include observation, interviews, and questionnaires. The results indicate that all research instruments are valid and reliable. Multiple linear regression analysis produces the equation Y = 1.376 + 0.232X1 + 0.427X2 + 0.259X3. The partial test (t-test) results show that digital marketing (t = 6.133; sig = 0.000), price (t = 8.028; sig = 0.000), and promotion (t = 7.628; sig = 0.000) have a significant effect on tourist interest. The simultaneous test (F-test) shows that the calculated F value of 31.165 is greater than the F table value of 2.98 with a significance level of 0.000 < 0.05, indicating that all independent variables simultaneously have a significant effect on tourist interest. The coefficient of determination (R²) is 0.552, indicating that 55.2% of the variation in tourist interest can be explained by digital marketing, price, and promotion, while the remaining 44.8% is influenced by other variables outside this study. Therefore, it can be concluded that price is the most dominant variable influencing tourist interest, followed by promotion and digital marketing.